2014
DOI: 10.1016/j.jceh.2013.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Combined Uphill and Downhill Varices as a Consequence of Rheumatic Heart Disease: A Unique Presentation

Abstract: Hemorrhage from downhill varices is a rare manifestation. The etiology of downhill varices is due to superior vena cava obstruction while uphill varices are secondary to portal hypertension. We report a rare case of 55-year-old female with bleeding downhill varices not associated with obstruction or compression of superior vena cava, but was due to severe pulmonary artery hypertension secondary to chronic rheumatic heart disease. ( J CLIN EXP HEPA-TOL 2014;4:63-65) E sophageal varices are classified as downhil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 4 publications
0
8
0
2
Order By: Relevance
“…However, a systematic review of individuals with atrial fibrillation receiving dialysis found similar efficacy in preventing venous thromboembolic events with direct oral anticoagulants (DOACs) versus warfarin [51]. Some of the other predisposing factors that are found less happened included retrosternal thyroids [16,21,23,40,41], Behçet's disease [6,22,32,42] and pulmonary hypertension [7,24,25,34]. Downhill varices in retrosternal goiter develop due to a similar obstruction in the thyroid veins resulting in the blood re-routing via the deep esophageal veins [16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a systematic review of individuals with atrial fibrillation receiving dialysis found similar efficacy in preventing venous thromboembolic events with direct oral anticoagulants (DOACs) versus warfarin [51]. Some of the other predisposing factors that are found less happened included retrosternal thyroids [16,21,23,40,41], Behçet's disease [6,22,32,42] and pulmonary hypertension [7,24,25,34]. Downhill varices in retrosternal goiter develop due to a similar obstruction in the thyroid veins resulting in the blood re-routing via the deep esophageal veins [16].…”
Section: Discussionmentioning
confidence: 99%
“…The definitive diagnosis is made via neck imaging and management mainly involves thyroidectomy to relieve the obstruction and resume normal blood flow. In addition, a mechanical obstructive mechanism increased blood drainage in the esophageal veins due to malignancy as well as pulmonary hypertension leading to venous backflow have also been proposed as etiologies for downhill varices [26,34,38].…”
Section: Discussionmentioning
confidence: 99%
“…Most cases of SVC obstruction are associated with some forms of malignancy including lung, lymphoma, and mediastinal metastases [ 6 , 7 ]. Nonmalignancy etiologies include pacemaker implantation [ 8 ], goiter [ 9 , 10 ], central venous catheters (dialysis catheter in particular) [ 11 14 ], rheumatic heart disease [ 15 ], congenital heart disease [ 16 ], thymoma [ 5 ], and mediastinal fibrosis [ 17 ]. There are however no direct association or reported cases linking hypercoagulable state as a contributing cause.…”
Section: Discussionmentioning
confidence: 99%
“…Venous drainage of the esophagus predominantly occurs by the azygos and hemiazygos systems. When there is an obstruction, these vessels can dilate and form varices in the esophagus (1,2). An obstruction in the SVC forces retrograde flow of blood into the right atrium through collateral channels to the IVC (1).…”
Section: Pathogenesismentioning
confidence: 99%
“…If the obstruction is above the level of the azygous vein, blood flow back to the heart will be confined to the upper esophagus, leading to formation of varices in the upper third of the esophagus. In contrast, if the obstruction is below or involving the azygous vein, varices will form along the entire esophagus (2,3).…”
Section: Pathogenesismentioning
confidence: 99%